Legal Assistance in Drafting Anti-Bullying Policies at Islamic Boarding Schools: A Case Study of Tarbiyyah Islamiyah Islamic Boarding School in Limbang Jaya 2 Village - Jafar, Abdul; Sarah, Sarah; Saputra, M Adi; Akbar, Firdaus (Unram Journal of Community Service, 2025)
This community service program aims to provide legal assistance in drafting anti-bullying policies at Tarbiyyah Islamiyah Islamic Boarding School in Limbang Jaya 2 Village. The program involves lecturers, students, and the Legal Aid Institute (LBH) to create a safe and bullying-free learning environment. Key activities include socialization, training, group discussions, and the drafting of anti-bullying policies based on national law and Islamic moral values. A participatory approach was employed by involving teachers, students, and parents throughout the process. The program's results indicate increased awareness and understanding of bullying, both from the perspective of positive law and moral-religious principles. The drafted policies cover bullying definitions, reporting mechanisms, sanctions, and case handling procedures. Initial implementation of the policies showed positive changes in students' attitudes and behaviors, as well as increased engagement from parents and teachers in creating a bullying-free environment. This program is expected to serve as a model adaptable for other educational institutions. Program sustainability is maintained through regular evaluations and the establishment of an anti-bullying committee at the school. This collaborative approach significantly contributes to fostering a safe, healthy, and harmonious educational environment